Phase change in fuel sprays at diesel engine ambient conditions: Impact of fuel physical properties - Rezaei, Javad; Rieß, Sebastian; Wensing, Michael (Journal of Supercritical Fluids, 2021)
In mixing controlled Diesel combustion concept, mixing processes are a key phenomenon that significantly effects power, efficiency and emissions. A consequence of fuel-air-mixing is fuel phase change, which is not fully understood yet. In this study, phase change mechanisms of sprays of different n-alkanes at high pressure and temperature conditions are investigated. Mie scattering imaging is utilized to obtain the maximum liquid penetration of Diesel surrogates (hexane, heptane, decane and dodecane) injected into nitrogen atmosphere in a constant volume chamber at fuel supercritical temperature and ambient pressures ranging from sub- to supercritical. Two 1D models are utilized to predict the liquid length based on the required enthalpy for full phase change. The theoretical models are validated against experimental data to identify phase change regimes. Along with ambient conditions, fuel properties significantly influence the phase change mechanism in a spray. Especially fugacity plays an important role regarding the droplet evaporation rate.
CRIS-Team Scopus Importer:2021-01-01
Keywords: Diesel spray; n-Alkanes; Phase change; Supercritical